Vitamin D Intake and Status of Children With Sickle Cell Disease in Montreal, Canada. Issue 8 (November 2018) - Grégoire-Pelchat, Pascale; Alos, Nathalie; Ribault, Virginie; Pastore, Yves; Robitaille, Nancy; Mailhot, Geneviève
Abstract : Sickle cell disease (SCD) and vitamin D deficiency share manifestations such as bone complications and bony pains. Canadian SCD children are characterized by compromised sun exposure all year long and potential dietary deficiency, which combined to SCD-causing high nutritional demands, may lead to impaired vitamin D status. The objectives of this study were to document vitamin D status and intake and assess the relationship between vitamin D status and SCD-related outcomes in Canadian children with SCD followed in a tertiary pediatric center. Our study population included 119 children (47% males, median age [interquartile range]: 11.1 [9.2-14.8]) mainly of Haitian and Sub-Saharan African origin who had at least one measure of serum 25-hydroxyvitamin D (25OHD) performed between June 2015 and February 2017. Predominant genotypes were homozygous hemoglobin S (60%) and sickle hemoglobin-C (32%). Vitamin D deficiency (25OHD<30 nmol/L) and insufficiency (30 to 49 nmol/L) were present in 31% and 37% of children, respectively. Vitamin D-sufficient children (25OHD>50 nmol/L) had higher hemoglobin levels, lower leukocyte, reticulocyte, and neutrophil counts, compared with vitamin D-deficient and insufficient children. Vitamin D intake was low and modestly correlated to serum 25OHD levels. Acute SCD complications in the preceding 2 years were not associated with vitamin D status in these children. Abstract : Supplemental Digital Content is available in the text.